A Narrow Quantitative Trait Locus in C. elegans Coordinately Affects Longevity, Thermotolerance, and Resistance to Paraquat - Vertino, Anthony; Ayyadevara, Srinivas; Thaden, John J.; Shmookler Reis, Robert J. (Frontiers in Genetics, 2011)
By linkage mapping of quantitative trait loci, we previously identified at least 11 natural genetic variants that significantly modulate C. elegans lifespan, many of which would have eluded discovery by knockdown or mutation screens. A region on chromosome IV between markers stP13 and stP35 had striking effects on longevity in three interstrain crosses (each P < 1E–9). In order to define the limits of that interval, we have now constructed two independent lines by marker-based selection during 20 backcross generations, isolating the stP13–stP35 interval from strain Bergerac-BO in a CL2a background. These congenic lines differed significantly from CL2a in lifespan, assayed in two environments (each P<0.001). We then screened for exchange of flanking markers to isolate recombinants that partition this region, because fine mapping the boundaries for overlapping heteroallelic spans can greatly narrow the implicated interval. Recombinants carrying the CL2a allele at stP35 were consistently long-lived compared to those retaining the Bergerac-BO allele (P<0.001), and more resistant to temperature elevation and paraquat (each 1.7-fold, P<0.0001), but gained little protection from ultraviolet or peroxide stresses. Two rounds of recombinant screening, followed by fine-mapping of break-points and survival testing, narrowed the interval to 0.18 Mb (13.35–13.53 Mb) containing 26 putative genes and 6 small-nuclear RNAs – a manageable number of targets for functional assessment.